Role of the 807 C/T Polymorphism of the α2 Gene in Platelet GP Ia Collagen Receptor Expression and Function - Corral, J.; González-Conejero, R.; Rivera, J.; Ortuño, F.; Aparicio, P.; Vicente, V. (Thrombosis and Haemostasis, 1999)
The variability of the platelet GP Ia/IIa density has been associated with the 807 C/T polymorphism (Phe 224) of the GP Ia gene in American Caucasian population. We have investigated the genotype and allelic frequencies of this polymorphism in Spanish Caucasians. The T allele was found in 35% of the 284 blood donors analyzed. We confirmed in 159 healthy subjects a significant association between the 807 C/T polymorphism and the platelet GP Ia density. The T allele correlated with high number of GP Ia molecules on platelet surface. In addition, we observed a similar association of this polymorphism with the expression of this protein in other blood cell types. The platelet responsiveness to collagen was determined by “in vitro” analysis of the platelet activation and aggregation response. We found no significant differences in these functional platelet parameters according to the 807 C/T genotype. Finally, results from 3 case/control studies involving 302 consecutive patients (101 with coronary heart disease, 104 with cerebrovascular disease and 97 with deep venous thrombosis) determined that the 807 C/T polymorphism of the GP Ia gene does not represent a risk factor for arterial or venous thrombosis.